Meningkatkan Ketahanan Usaha Ultra Mikro Terhadap Guncangan Akibat Pandemi di Papua Barat - Edy Nasrudin; Rian Andriono (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2022)
Mobility restrictions to prevent the risk of the Covid-19 pandemic have negatively affected the volume of economic activity. Reflecting on the history of previous economic crises, ultra-micro enterprises have become actors that are able to face changes. However, the long pandemic period makes ultra-micro enterprises unable to run solo and need support. Government support in order to keep ultra-micro enterprises surviving and growing is carried out through a recovery program. This study aims to determine the impact of government policies in maintaining the resilience of ultra-micro enterprises and also measure the effectiveness of ultra-micro financing during the pandemic. The study used survey data gathered from debtors through interviews and analyzed using qualitative descriptive methods. The result showed that the recovery program is able to increase ultra-micro enterprise's resilience, positively impact business development, and also reducing unemployement. However, ultra-micro financing needs to be supported by specific strategies to expanding the reachness and accessibility.